Cloning of rd29A-CBF3 gene constructs in binary vector (pCAMBIA0390) for improving high altitude agriculture during cold stress - GUPTA, SANJAY MOHAN; PANDEY, PANKAJ; AHMED, ZAKWAN (The Indian Journal of Agricultural Sciences, 2012)
CBF3 gene is rapidly induced upon exposing plants to low temperature, followed by expression of CBF-targeted genes, the CBF regulon, resulting in an increase in plant freezing tolerance. It has been possible to engineer cold tolerance in transgenic plants by manipulating the expression of CBFs. In this attempt CBF3 gene has been isolated from Arabidopsis and cloned in binary vector (pCAMBIA0390) under the control of stress inducible rd29A promoter. CBF3 gene cloned pCAMBIA0390 and nptII gene containing pCAMBIA2200 vector DNA was transformed into the Agrobacterium strain LBA4404 that could be used to generate cold-tolerant transgenic plants for improving high altitude agriculture during cold stress.